Strategies, achievements and challanges in bean research; the CIAT perspective - Schoonhoven, Aart van (International Center for Tropical Agriculture, 1985)
Strategies, achievements, and challenges in bean research at CIAT are analyzed and discussed. Research strategy emphasis has been to reduce losses caused by diseases and pests. This strategy has, in general, not lead to yield increases. A change in research emphasis is, therefore, proposed. This future research should be increased in 3 main areas: (1) breeding for increased yield potential; (2) study of the photoperiod-temp. adaptation of beans, particularly at higher lat. to widen available genetic variability; (3) increasing consumer acceptability of beans by improving bean nutrition. (CIAT)